Nuovi orizzonti della ricerca scientifica in educazione. Raccordare ricerca e decisione didattica: il Manifesto S.Ap.I.E. - Antonio Calvani; Roberto Trinchero; Giuliano Vivanet (LED Edizioni Universitarie, 2018)
Here some theses introduced in the S.Ap.I.E. (Società per l'Apprendimento e l'Istruzione informati da Evidenza) Manifesto are developed. Firstly, we summarize the relevant advances in educational research characterizing the new millennium, related to Evidence-Based Education and its convergence with other fields. These gave rise to a new scientifically-based perspective in education and to a new domain that we named Instructional and Learning Science. Then, we examine some developments now possible concerning fundamental principles of instruction and recommendations to which teachers should refer; the critical revision of some widespread beliefs not based in evidence at all; and the possibility of defining rational frameworks, informed by evidence, to support educational decisions. Finally, we introduce some challenges for the new generation of educational scientists, in the hope that the current stalemate in Italian educational research can be overcome. These concern mainly: (i) the graduate programs in education in which methods of educational research, within a critical culture on knowledge reliability, should be at the basis; and (ii) new forms of collaboration between universities and schools which, leaving current models of limited impact, should be oriented towards clearly defined objectives and effective programs.